In vitro activity of three different antimicrobial agents against ESBL producing Escherichia coli and Klebsiella pneumoniae blood isolates - Kizirgil, A; Demirdag, K; Ozden, M; Bulut, Y; Yakupogullari, Y; Toraman, ZA (Elsevier Gmbh, 2005)
resistance, including beta-lactam and non-beta-tactam antibiotics. This resistance can cause limitation in the choice of drugs appropriate for using in clinical practice, especially in life-threatening infections. In this study we aimed to investigate in vitro activity of meropenem, ciprofloxacine and amikacin against ESBL-producing and non-producing blood isolates of Escherichia coli and Klebsiella pneumoniae strains. Fifty-eight E. coli (21 ESBL-producing, 37 non-ESBL producing) and 99 K. pneumoniae (54 ESBL-producing, 45 non-ESBL producing) strains were included in the study. The presence of ESBL was investigated by double disk synergy test and E-test methods. Antibiotic susceptibility test was done by microdilution method according to NCCLS guideline. In vitro susceptibilities of ESBL producing E. coli and K. pneumoniae strains were found as 100% for meropenem, 33.3% and 25.9% for ciprofloxacine, 94.5% and 83.3% for amikacin. It was observed that; meropenem was equally active agent in both ESBL-producing and non-producing strains, and its activity was not affected by ESBL production. Whereas amikacin activity was minimally affected and ciprofloxacine activity was markedly decreased by ESBL production. In conclusion, meropenem seems to be better choice of antibiotic should be used for ESBL positive life-threatening infections, because of remaining highest activity. (c) 2004 Elsevier GmbH. All rights reserved.
Keywords: E. coli; K. pneumoniae; ESBLs; antibiotic susceptibility; MIC; meropenem; ciprofloxacine; amikacin